REPRESENTATION AND IMPACT OF SYMBOLIC VIOLENCE IN GOLDMAN’S “THE LION IN WINTER” STORY - Anastasia Juwita Ningsih; Tomi Arianto (Asosiasi Ide Bahasa Kepri, 2022)
Symbolic violence is a type of violence that is difficult to detect. However, this type of violence is really visible. It can be found in numerous forms and tactics throughout the entertain environment which is drama. Especially in “The Lion in Winter” drama. It is reflecfed the issue about the woman who had symbolic violence from her environment. Not only symbolic violence, the woman got gender inequality that continues to discredit her and patriarchal construction system that legitimizes gender inequality. Feminist approach applied to support the data in this research. This research used Bourdieu (1991) theory to analyze the representation of symbolic violence. Bourdieu used this notion to explain the mechanism by which the elite, or the ruling upper class, transmits their lifestyle to the ruling lower class. The method in this research applied in the descriptive qualitative method from Creswell (2009). To collect the data, this research used theory from Ratna (2004) which is regard to the actions and dialog performance. The story in the drama was studied using library research and a feminism perspective. The Result of the research showed that symbolic violence reflected from the main character who is becoming discrimination without relazing if she is in indoctrinate. The impacts of symbolic violence make the main character become betrayal, lying, disrespect, hatred speech, and insult.